Oncoplastic Breast Surgery : An Early Experience in CMH Dhaka (Journal of Brahmanbaria Medical College, 2026)
Background: Oncoplastic Breast Surgery (OBS) integrates oncologic principles with plastic surgical techniques to optimize cancer control and cosmetic outcomes. Despite global adoption, OBS is not yet widely used in many low- and middle-income countries (LMICs), including Bangladesh. The purpose of the study to determine the feasibility, aesthetic results and safety of oncoplastic breast surgery at CMH, Dhaka. Materials and methods: This observational retrospective study was performed in Combined Military Hospital (CMH) Dhaka, between January 1, 2021 and December 31, 2022. Fifty-six women who had histologically proven breast cancer and underwent OBS were included. Demographic, clinicopathological, surgical, and outcome details were reviewed. Results: The average age of the patients was 43.2 ± 6.8 years, and 50.0% were overweight. Most were invasive ductal carcinoma (98.2%), with a mean size of 2.6 cm ± 0.7. Volume displacement techniques predominated (67.9%). Postoperative margin clearance was achieved in all cases, with no requirement for reoperation.The overall 30-day complication rate was 16.1%, with no major morbidity. Patient-reported cosmetic satisfaction was high, with 64.3% rating outcomes as excellent. No local or distant recurrence was observed at a mean follow-up of 18 months. Conclusion: OBS is a safe and effective surgical modality in the Bangladeshi context, ensuring oncologic safety and aesthetic output. These results support broader implementation of OBS in LMIC settings.JBRMC, Volume 08 Issue 01 January 2026 ; 9-14